2021
DOI: 10.3390/cancers13194887
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Architecture and Evolutionary Dynamics in Acute Myeloid Leukemias

Abstract: Acute myeloid leukemias (AML) results from the accumulation of genetic and epigenetic alterations, often in the context of an aging hematopoietic environment. The development of high-throughput sequencing—and more recently, of single-cell technologies—has shed light on the intratumoral diversity of leukemic cells. Taking AML as a model disease, we review the multiple sources of genetic, epigenetic, and functional heterogeneity of leukemic cells and discuss the definition of a leukemic clone extending its defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 173 publications
0
11
0
Order By: Relevance
“…3D hydrogel co-cultures are frequently used in tissue engineering for reproducing stem cell niche environments, such as satellite cell niche in muscle cell regeneration [ 18 , 26 , 35 ]. Hydrogels are also a suitable biomaterial for in vitro studies, as they can be easily degraded, and cells can be harvested and used for further experiments [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 34 , 36 , 37 , 38 ]. Moreover, the three-dimensionality of hydrogels creates a hypoxic gradient, naturally present in the marrow, thus better mimicking the BM niche [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D hydrogel co-cultures are frequently used in tissue engineering for reproducing stem cell niche environments, such as satellite cell niche in muscle cell regeneration [ 18 , 26 , 35 ]. Hydrogels are also a suitable biomaterial for in vitro studies, as they can be easily degraded, and cells can be harvested and used for further experiments [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 34 , 36 , 37 , 38 ]. Moreover, the three-dimensionality of hydrogels creates a hypoxic gradient, naturally present in the marrow, thus better mimicking the BM niche [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-cultures with mesenchymal stem cells (MSCs), a component of the BM niche characterized by multi-differentiation potential and immunomodulatory activity, can support HSC maintenance in bi- (2D) and tri-dimensional (3D) conditions through secretion of soluble factors and by inter-cellular interactions [ 17 , 18 ]. Therefore, culture systems resembling BM architecture can improve HSC survival and proliferation and reproduce in vitro the complex biological in vivo cross-talks between stem cells, stroma, and microenvironment to better investigate the impacts of somatic mutations in AML-related genes [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that there are continuous intercellular communications between normal cells as well as cells in a neoplastic growth [ 11 , 12 ]. It has been shown that such intercellular signaling plays important role in emergence of novel clone(s) in malignant disorders and therefore such signaling pathways could possibly be the therapeutic targets in the future [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in AML samples, based on mutational history, pre-leukemic clones, MDS clones, and multiple AML clones can be detected in the same patient. Although all clones in the same patients share the same founder mutation, such as TET2 MT , the subsequent mutations are not the same among them [166,167]. Because the therapeutic responses of different clones are not all the same, some clones are completely eliminated during treatment and only AML cells from certain clones are sustained, which eventually leads to disease relapse.…”
Section: Clonally Heterogenic Architecture Of Hematopoietic Malignanciesmentioning
confidence: 99%
“…In addition, both restoration and inhibition of TET protein activity have been proposed for the treatment of TET MT hematopoietic malignancies. Preclinical studies suggested that vitamin C (a cofactor in TET catalysis) represses TET2 MT cell growth by enhancing the activity of remaining WT TET2 molecules, as well as TET1 and TET3 [140,141,143,167,174]. The anti-cancer property of vitamin C can be enhanced when combined with the SIRT activator SRT1720, P300/CBP inhibitors C646 or HATi, or the HDAC I/II inhibitor trichostatin A, through regulation of the site-specific acetylation of TETs [175].…”
Section: Oncogenic Collaboration Of Mutations With Tet2 Mt In Animal ...mentioning
confidence: 99%